PROTECTION AGAINST RECIPIENTS NOTARY DEED THAT ALLEGEDLY PROTOCOL TO THE LEGAL ISSUE IN SEMARANG - Megacaesa Fuditia Fuditia; Ni Made Srinitri; Anis Mashdurohatun (Jurnal Akta, 2020)
Notary Appointment as Notary Protocol holders and storage required to accept the delegation of the protocol, because at the beginning of his run, every Notaries are required to make a statement about its willingness to accommodate the move Notary Protocol, quit, or died. As a holder of the protocol but can learn a lot there is also a consequence of the receipt of such deed is when there is a legal problem, as the holder of the protocol also participated as a defendant or summoned by investigators in order to bring that existed at the Notary deed holder protocol. However, it has become a legal obligation Notary.          The purpose of this research are: 1) To analyze and assess the extent of legal protection against protocol receiver notary deed allegedly related legal issues in the city of Semarang. 2) To analyze and assess the barriers in the legal protection of the receiving notary deed allegedly protocols about legal issues in the city of Semarang. 3) To formulate legal protection against protocol receiver notary deed was allegedly associated legal problems in the future.Notary receiver and storage protocol is not responsible for the contents of the deed of the substance or the above protocol receives. UUJN enactment, not without obstacles in its implementation. It was mainly related to the legal protection of a notary. Those barriers between them, yet the formation of the Implementing Regulation and Role Change THIS UUJN to socialize UUJN Changes in certain areas less. Legal protection should be given to the notary deed protocol receiver must be in accordance with Law Notary Article 66 paragraph (1) of Law No. 2 of 2014 on the Amendment of the Law of the Republic of Indonesia Number 30 Year 2004 on Notary.Keywords : Deed, Legal, Notary, Legal Protection, the Protocol.